«Speaking does not mean being a human»: critical analysis of current studies of the “animal language” in accordance with L.S. Vygotsky’s ideas - Еlena E. Sokolova; Еlena Yu. Fedorovich (Национальный психологический журнал, 2016)
This paper is based upon the ideas of the psychological school of L. S. Vygotsky, A. N. Leontiev and A. R. Luria and presents a critical analysis of currently popular and allegedly successful projects of teaching human language to apes. The paper shows that the authors of such studies and their promoters ignore qualitative differences between psychological mechanisms of human and animal communication, as well as their functions in behavioral regulation of both. This is explained, in particular, by the fact that the human-animal comparison originates from some visible and functional similarities of certain aspects of their communicative behavior. Moreover, the observed differences are recognized as quantitative distinctions, but not qualitative ones. In this paper a critical analysis of data submitted by such projects is presented. The outcome is as follows. Though apes, especially in vitro, can use some symbolic means (language symbols) to manipulate the behavior of others, none of the animals, subjected to such experiments have acquired an ability to control themselves in the context of certain social (conventional) requirements. Meanwhile, according to L. S. Vygotsky, the arbitrary regulation of one’s own behavior with the use of symbolic means as «psychological tools» is what determines a human as a being, qualitatively different from an animal. Moreover, this arbitrary regulation has emerged in the course of historical development through human labor (common, socially-induced and tool-mediated) activity. Hence, the conclusion is that if the most important features of human language (its use on the way of mastering one’s own behavior and regulating one’s own mental processes) is ignored, this leads to inadequate interpretation of the data collected in animal behavior studies, as well as to biological reductionism of human activity explanation.